Policy Analysis Of Fuel Subsidy In Indonesia - Yuniza, Mailinda Eka; Sekar Nuswantari, Shafa Femalea; Jatmiko, Pius Katon (Jurnal de jure, 2023)
Fuel subsidies have become one of the heaviest burdens in Indonesia's State Budget (APBN), aimed at ensuring equitable accessibility of fuel to all segments of society. However, the mistargeting of the fuel subsidies can lead to the Indonesian population's dependence on subsidised fuel, thus undermining the efforts to address inequitable access to fuel. This study aims to analyse the realization of the fuel subsidy scheme in Indonesia and explore possible measures to achieve a more targeted and volume-appropriate fuel subsidy program. This paper focuses on the analysis of existing regulations concerning fuel subsidies in Indonesia, the weaknesses of these regulations, and the distribution of fuel subsidies as well as its current implementation. A live case study approach was employed. The research examined the gaps between the ideal state (das solen) and the actual state (das sein) of fuel subsidies by first examining the applicable legal norms. Subsequently, an analysis was conducted to determine whether or not the implementation is appropriate. Notably, Presidential Regulation Number 191 of 2014 does not specify the criteria for recipients of subsidised fuel of the JBKP (Special Assignment Fuel Type). This legal absence has resulted in an imprecise targeting and volume of the distribution of subsidised fuel.